Swedish Bird Survey: Summer point count routes (Sommarpunktrutterna) - Åke Lindström; Martin Green (Lund University, 2020)
The summer and winter point count routes (“punktrutterna”) are two of several schemes within the Swedish Bird Survey (see below), run by the Department of Biology at Lund University. The point count routes were initiated in 1975 as a standardized method for detecting and reporting changes in the abundance of birds and their distributions in Sweden over time. The point count routes can be surveyed in summer and/or winter.The surveys are initiated and carried out by volunteer ornithologists who use standardized methods to count birds along routes of their own choice.Nearly 3200 point count routes have been surveyed at least once up to and including the year 2024, and approximately 1250 of these have been surveyed during the summer. The dataset presented here is for the summer point count routes.In this dataset, some information is placed in the table ExtendedMeasurementOrFacts (eMoF), which is part of the Source Archive available to download directly from the dataset’s page here on gbif.org. The Source Archive contains the data exactly as uploaded to gbif (verbatim). Should you choose to download the dataset as GBIF Annotated Archive instead, the data has been interpreted and quality controlled by gbif, but, the data in the eMoF will not be included as the eMoF extension is not yet supported by gbif.
Keywords: Samplingevent; Samplingevent; SAMPLING_EVENT; Biological Sciences; Biologi